Posttraumatic stress in breast cancer patients - Bulotienė, Giedrė; Matuizienė, Jurgita (Acta medica Lituanica, 2014)
Background. Breast cancer diagnosis is a potential life-threatening event associated with significant distress. The present study aimed to identify the prevalence of posttraumatic stress and its association with clinical and social factors in early breast cancer patients and one year after surgery. Materials and methods. Four hundred twenty one newly diagnosed breast cancer patients completed three questionnaires: Impact of Event Scale – revised (IES-R), Beck Depression Inventory II (BDI-II), Vrana & Lauterbach Traumatic Events Scale-Civilian (TEQ). Women were questioned before surgery and one year later. Patients were 18–80 years old resident Lithuanian women with histologically confirmed breast cancer and no history of other cancers. Additional requirements were as follows: ability to read Lithuanian and being capable of completing a questionnaire. Results. 51.5% of newly diagnosed breast cancer patients had from moderate to severe symptoms of PTSD (score average of IES-R ≥ 1.5). After one year it decreased and there were 33.5% of patients who had symptoms of PTSD. The scores of all subscales were decreased a bit as well. Immediately after statement of diagnosis, PTSD correlated with sadness, often cry and earlier traumatic experience. One year later, PTSD correlated with poor self perception, sadness and traumatic experience during this year. Pessimistic mood, lack of energy, difficulties to concentrate were significant to breast cancer patients. Conclusions. A significant number of breast cancer patients suffers from PTSD symptoms. After one year, the amount of patients suffering from PTSD decreased almost twice. Depression and traumatic experience are the predictors of PTSD. The findings show that early evaluation of psychoemotional needs of breast cancer patients is necessary and early interventions are meaningful.